INNER FORM IN WORD-BUILDING (Scientific journal of the Fergana State University, 2023)
In this article, the peculiarities of the word-building "inner form", the semantic-structural aspects of the formations formed by such methods, and the existing views on this matter in linguistics, are analyzed on the basis of linguistic evidence.